2020
DOI: 10.1038/s41598-020-78840-y
|View full text |Cite
|
Sign up to set email alerts
|

Fontan-associated liver disease and hepatocellular carcinoma in adults

Abstract: The Fontan operation creates a unique circulation, and is a palliative therapy for patients with single-ventricle congenital heart disease. Increased venous pressure and decreased cardiac output and hepatic venous drainage result in sinusoidal dilatation around the central veins. This causes congestion and hypoxia in the liver, leading to Fontan-associated liver disease (FALD). Non-invasive and invasive markers enable diagnosis and evaluation of the fibrosis status in chronic liver disease; however, these mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 96 publications
(126 reference statements)
2
31
0
Order By: Relevance
“…However, there was no Accumulated study have suggested the development of liver fibrosis according to the time since surgery. 38 A previous study has histologically examined 13 patients and disclosed all of cases had at least some degree of sinusoidal liver fibrosis at mean time of 16.9 years (range 6.9-25) after Fontan procedure. 6 Another histological study found that the time since Fontan procedure >18 years was associated with a higher degree of liver fibrosis as compared with ≤18 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no Accumulated study have suggested the development of liver fibrosis according to the time since surgery. 38 A previous study has histologically examined 13 patients and disclosed all of cases had at least some degree of sinusoidal liver fibrosis at mean time of 16.9 years (range 6.9-25) after Fontan procedure. 6 Another histological study found that the time since Fontan procedure >18 years was associated with a higher degree of liver fibrosis as compared with ≤18 years.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic congestion due to heart failure is one of the pathogeneses of HCC. 13 The present case was complicated by hypertrophic cardiomyopathy and mitral regurgitation. Furthermore, the patient had past history of surgery for an atrial septal defect.…”
Section: Discussionmentioning
confidence: 71%
“…It is known that increased venous pressure and decreased cardiac output and hepatic venous drainage result in sinusoidal dilatation around the central veins. 13 Finally, this may have caused liver cirrhosis and the development of HCC. Chronic congestion and/or vessel abnormality may be a reason for the development of HCC in this case.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying pathophysiology of these complications may reflect the elevated central venous pressure and decreased cardiac output that follow the Fontan procedure. After surgery, the hepatic venous flow empties directly into the Fontan circuit, such that the liver is susceptible to the effects of central venous hypertension [ 16 , 17 ]. High central venous pressure also leads to chronic passive congestion subsequent to sinusoidal dilatation, with increased intrahepatic resistance and reduced portal flow [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…After surgery, the hepatic venous flow empties directly into the Fontan circuit, such that the liver is susceptible to the effects of central venous hypertension [ 16 , 17 ]. High central venous pressure also leads to chronic passive congestion subsequent to sinusoidal dilatation, with increased intrahepatic resistance and reduced portal flow [ 16 , 17 ]. Decreased cardiac output can further contribute to the reduction of portal flow.…”
Section: Introductionmentioning
confidence: 99%